The complete chloroplast genome sequence of a hybrid blackberry (Rubus spp.) cultivar - Xun-ju Liu; Xiao-rong Wang; Hao-ru Tang; Qing Chen (Mitochondrial DNA. Part B. Resources, 2021)
Blackberry (Rubus spp.) is an important hybrid fruit crop popular in the US Pacific Northwest and the European region with complex origins. In this study, we report the complete chloroplast genome sequence of a hybrid blackberry cultivar ‘Arapohol’ using next-generation sequencing technology. The complete chloroplast genome size is 156,621 bp. The genome contains 134 genes, including 40 tRNA genes, 86 protein-coding genes, and 8 rRNA genes. Phylogenetic analysis based on 11 complete chloroplast genomes revealed that taxa is closely related to Rubus niveus. The complete chloroplast genome of this Rubus sp. provides valuable information for understanding the origination of this crop species.